Morphological Characterization, Evaluation and Selection of Hibiscus ( Hibiscus rosa-sinensis L) Hybrids - Cabarrubias, Elena May N.; Magdalita, Pablito M.; Lalusin, Antonio G.; Medina, Norma G. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 29 No 2 (2017), 2017)
Fifty-seven hibiscus hybrid progenies from different crosses were characterized and evaluated for morphological traits to select hybrids with unique color and form. A total of 14 progenies with the following pedigrees were selected: 22xDT-9, (LLxEFA)xGC-2, (LLxEFA)xGC-8, DSxGC-7, 20xGC-5, (GCxBGB)xHP-4, GCxDS-4, ABAxMDM-1, ABAxMDM-3, 23xGC-2, CVxNB-1, CVxNB-2, CVxMP-4 and CVxNB-6. Phenotypic data were analyzed for principal component analysis (PCA) and agglomerative cluster analysis. Correlation using PCA revealed signif icant positive association between flower size and leaf size, and between petiole length and leaf size. PCA depicted three major PCs with eigenvalue >1 contributing 78% of the total cumulative variability among different hybrids. The PC-I showed positive factor loadings for all the traits. The contribution of flower size, leaf size and style length was highest in PC-I. Cluster analysis grouped the 57 hybrids into f ive clusters. Cluster-I had the highest number of members (16), consisting of yellow-orange and purple flowers with a mean size of 131.09 mm. Cluster-II had 15 members, possessing white and red-purple hybrids with a mean size of 140.54 mm. Cluster-III was composed of f ive yellow members with a mean size of 131.12 mm. Cluster-IV had 13 members, comprising yellow and yellow-orange hybrids whose flowers are small and have a mean size of 115.20 mm. Cluster- V consists of eight red- and red-purple-colored hybrids with mean size of 130.21 mm. The study revealed that hybrids with large flowers and longer petioles tend to have wider leaves, and these results were in agreement with the dendrogram groupings of the 57 hybrids. Keywords: Agglomerate cluster analysis, Hibiscus rosa-sinensis L. , hybrids, principal component analysis